Marjinalisasi dan Pemberdayaan Masyarakat Adat dalam Penyelenggaraan Pemerintahan Nagari di Sumatera Barat - Rafni, Al; Suryanef, Suryanef; Yusran, Rahmadani; Indrawadi, Junaidi (Jurnal Demokrasi, 2008)
This article is based on a study related to marginalization of traditional society in the implementation of Nagari government in West Sumatera, especially in connecting with political/government, economic, and socio-cultural aspects. This study was conducted through an exploratory survey in five regencies and fifteen Nagari in West Sumatera. Data in this study was collected through deep interview, questionnaire, observation, study of documentation and analyzed with descriptive analysis. Kata kunci: Marjinalisasi, masyarakat adat, pemerintahan nagari, pemberdayaan